The use of cloud-based learning media and its implications for elementary students' digital literacy - Ragil Dian Purnama Putri; Fajar Kurnia Al Farisi; Tri Lestari; Safika Maranti; Agus Kichi Firmansyah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
The use of cloud-based learning media is a relevant digital learning strategy for supporting the development of digital literacy among elementary students. This study aims to analyze the digital literacy skills of elementary school students using cloud-based learning media in Kulon Progo. The study employs a qualitative approach, involving elementary school students, classroom teachers, and ICT administrators as participants. Data were collected through in-depth interviews, learning observations, and documentation studies, subsequently analyzed through data reduction, data presentation, and conclusion drawing using source and technique triangulation. The results reveal that students are accustomed to using digital devices to support learning, especially in accessing information, taking online quizzes, and completing cloud-based assignments. The use of cloud-based media contributes to increased student engagement, motivation, and learning experiences. However, the ability to critically evaluate digital information, creativity in producing digital content, and the use of artificial intelligence-based technology still require strengthening. In addition, digital literacy development is influenced by the availability of ICT infrastructure, teacher competence, and family support. Thus, the use of cloud-based learning media has the potential to support the development of digital literacy in elementary students if balanced with appropriate guidance and support from schools and families.